Mirror of the Self: Exploring the Influence of Self-Esteem and Narcissism on Social Media Addiction in college student - Ulva Widia Mentari; Farid Imam Kholidin; Eko Sujadi (Universitas Islam Negeri Madura, 2024)
Social media addiction is a concerning condition because it will disturb a person's mental health. This study aims to analyze the effect of self-esteem and narcissism on social media addiction. This study uses quantitative research using survey and correlational research designs. The subjects of this study amounted to 65 people and the research data were revealed using the self-esteem scale, narcissistic scale, and social media addiction scale. The results showed that there was a negative correlation between self-esteem and social media addiction, then statistics also hurt social media addiction. negative impact on social media addiction. It is recommended that future researchers conduct an in-depth investigation of the complex interactions between narcissism, self-esteem, and social media use. narcissistic, self-esteem, and social media use, and develop more effective strategies to reduce the negative effects of social media addiction. strategies to reduce negative effects.